Chemical warfare between fungus-growing ants and their pathogens. (December 2020) - Batey, Sibyl F.D.; Greco, Claudio; Hutchings, Matthew I.; Wilkinson, Barrie
Abstract: Fungus-growing attine ants are under constant threat from fungal pathogens such as the specialized mycoparasite Escovopsis, which uses combined physical and chemical attack strategies to prey on the fungal gardens of the ants. In defence, some species assemble protective microbiomes on their exoskeletons that contain antimicrobial-producing Actinobacteria. Underlying this network of mutualistic and antagonistic interactions are an array of chemical signals. Escovopsis weberi produces the shearinine terpene-indole alkaloids, which affect ant behaviour, diketopiperazines to combat defensive bacteria, and other small molecules that inhibit the fungal cultivar. Pseudonocardia and Streptomyces mutualist bacteria produce depsipeptide and polyene macrolide antifungals active against Escovopsis spp. The ant nest metabolome is further complicated by competition between defensive bacteria, which produce antibacterials active against even closely related species. Highlights: Specialist fungal pathogens attack the nests of fungus-growing ants. Ants form mutualistic relationships with defensive actinomycete bacteria. Specialised metabolites underpin these mutualistic and antagonistic interactions.